Energy Research at CREATE. Issue 1 (22nd November 2017) - Lim, Adeline; Lim, Khiang Wee
Abstract : Energy Research at the Campus for Research Excellence and Technological Enterprise (CREATE) : CREATE is a research campus of institutional partnerships with leading academic institutions. This special collection of Energy Technology highlights the energy research performed at the CREATE Campus in Singapore, with contributions on new developments in the areas of energy efficiency and renewable energy conversion and storage.